Improving Agriculture and Food Security Risk Financing in Southern Africa - World Bank (World Bank, Washington, DC, 2020)
The objective of this report is to provide a review of and recommendations for improving the agriculture and food security risk financing framework in the Southern Africa Development Community (SADC) Member States. This report presents the compilation of various analyses and activities realized in the context of a World Bank Group Advisory Services program to the SADC Region during 2019 and 2020, which included: (i) a stocktaking of the agroclimatic information systems of the region; (ii) the implementation of four innovation challenges to identify the most promising solutions to advance the risk finance agenda for food security and agriculture in the region; (iii) the implementation of one of the innovative solutions to one SADC Member State (the Democratic Republic of Congo); and (iv) the development of a regional risk financing policy note for agriculture and food security in SADC. The work was conducted by a multisectoral tea